2019
DOI: 10.3390/f10080652
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Radionuclides in the Trees of Fukushima Forests 1. Field Study

Abstract: The earthquake and tsunami on 11 March 2011 led to a meltdown followed by a hydrogen explosion at the Fukushima–Daiichi nuclear power plant in Japan, causing the dispersal of abundant radionuclides into the atmosphere and ocean. The radionuclides were deposited onto trees and local residences in aerosol or gaseous forms that were partly absorbed by rain or melting snow. Here, we show that the radionuclides attached to the surfaces of trees, in which some radiocesium was incorporated into the xylem through ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The radiocesium was also localized in the dead cells, which represented the artificially changed sapwood of cypress in Fukushima forest ( Figure 2B). This is in agreement with the observation [5] that the movement of radiocesium could accumulate in the heartwood of the tree stem. The radionuclide could also be further deposited in trees containing high levels of potassium.…”
Section: Flow Of Radiocesiumsupporting
confidence: 93%
See 3 more Smart Citations
“…The radiocesium was also localized in the dead cells, which represented the artificially changed sapwood of cypress in Fukushima forest ( Figure 2B). This is in agreement with the observation [5] that the movement of radiocesium could accumulate in the heartwood of the tree stem. The radionuclide could also be further deposited in trees containing high levels of potassium.…”
Section: Flow Of Radiocesiumsupporting
confidence: 93%
“…The radiocesium was markedly deposited onto trees and local residences in an aerosol form that was partly absorbed by rain or melting snow [2][3][4]. The radionuclide moved from the surface bark to the inner xylem in tree samples obtained from September 2011 to November 2015, 6 to 51 months after the accident [5]. Through the forest tree analyses, we found that radiocesium could be incorporated into the surfaces of trees and also could migrate throughout the tissues of the entire tree.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…The earthquake and tsunami on 11 March 2011 led to a meltdown followed by a hydrogen explosion at the Fukushima-Daiichi nuclear power plant in Japan, causing the dispersal of abundant radionuclides into forests and local residences by gaseous or aerosol forms [1][2][3][4]. Radioiodine and radiocesium were likely incorporated and fixed in forest trees.…”
Section: Introductionmentioning
confidence: 99%